Enhancing Academic Engagement through an Interactive Digital Manual: A Study on General Studies Students at the University of Ilorin - Medinat F. Salman; Lasiele A. Yahaya; Nafisat A. Adedokun-Shittu; Muhinat Bolanle Bello; Mayowa O. Ogunjimi; Foluke Bolu -Steve; Adedapo A. Atolagbe; Musa Siddiq Abdullahi; Hafsat Imam Alabi; Olufunmilola. L. Dominic; Olukunmi 'Lanre Olaitan (Yayasan Adra Karima Hubbi, 2025)
Background: Student engagement is crucial for academic success, yet many undergraduates exhibit low participation, poor attendance, and disengagement in General Studies (GNS) courses. Traditional teaching methods often fail to address the needs of diverse learners, particularly in large classes. The University of Ilorin recognizes the need for innovative approaches to improve academic engagement and outcomes. Purpose: This study aimed to investigate the development and implementation of an Interactive Digital Manual (IDM) tailored to the specific needs of GNS students. It examined the effects of the IDM on student attendance, engagement, and academic participation, alongside students’ perceptions of its impact on learning and retention. Method: A mixed-methods approach was employed, involving 1,332 participants selected from 200-level GNS courses across 17 faculties. Quantitative data were collected through surveys and attendance logs, while qualitative data were gathered via open-ended questions and focus group discussions. Statistical analyses were used to evaluate the IDM's impact. Results: The findings reveal significant improvements in attendance and engagement following the IDM's implementation. Median attendance increased by 866, while engagement scores rose from a mean of 32.5 to 75.8. Students highlighted features such as self-paced learning, interactive exercises, and real-time feedback as critical to their improved understanding and retention of course material. Conclusion: The IDM effectively enhances student engagement, attendance, and learning outcomes in GNS courses. Its innovative design addresses diverse learning needs, offering a structured, accessible, and interactive platform. This study underscores the value of digital tools in fostering academic success and calls for their broader integration into educational strategies.